2017
DOI: 10.4028/www.scientific.net/jera.31.77
|View full text |Cite
|
Sign up to set email alerts
|

Application of Waste Glass Powder as a Partial Cement Substitute towards more Sustainable Concrete Production

Abstract: Use of waste materials in concrete is now a global trend for efficient waste management so as to achieve a sustainable green environment and with the added advantages of preserving the natural resources as well as producing a better performing concrete. This study examined the properties of concrete containing ground waste glass powder (GP) as partial replacement for cement. The waste glass was finely grounded into powder and the morphology imagery of the powder materials was carried out using scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…In addition, Gahoi and Kansal (2016) concluded that the percentage of water absorption decreases compared to the reference concrete for both classes of concrete M20 and M30. Olofinnade et al (2017) found that an increase in porosity can be observed at an increase of glass powder content. Du and Tan (2014) studied the properties of concrete with the partial replacement of cement by glass powder.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, Gahoi and Kansal (2016) concluded that the percentage of water absorption decreases compared to the reference concrete for both classes of concrete M20 and M30. Olofinnade et al (2017) found that an increase in porosity can be observed at an increase of glass powder content. Du and Tan (2014) studied the properties of concrete with the partial replacement of cement by glass powder.…”
Section: Introductionmentioning
confidence: 96%
“…Rahman and Uddin (2018) concluded that 30% of cement replacement achieves maximum tensile strength by splitting compared to the control concrete at 28 days. Olofinnade et al (2017) showed that it is possible to produce medium-strength durable concrete for structural applications using 20% glass powder as a cement replacement. The study conducted by Aliabdo et al (2016) shows the effect of the use of glass powder in concrete as a replacement and addition to cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main processes in manufacturing of glass are batch preparation, melting, refining, forming, and post forming, which are highly energy consuming and pollutant 5 . For example, silica must be melted at high temperature (1,500°C) for 72 hr to manufacture plate glass.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that discarded glass in finely ground form can be deployed as a pozzolan to partially substitute cement or as filler material in concrete and mortar (Jani andHogland 2014, Olofinnade et al 2017b). However, reports by Taha and Nounu (2008) and Olofinnade et al (2017aOlofinnade et al ( , 2018 mentioned that factors limiting the use of discarded glass in cement-based concrete and mortar are a reduction in strength and cracking caused by alkali-silica reaction (ASR). Furthermore, concrete structures are exposed to increased temperature conditions, therefore heat or fire resistance properties of concrete structures are always considered at the design stages.…”
Section: Introductionmentioning
confidence: 99%